Effect of sleep quality on vision-related quality of life in a sample of Qassim University students: an ocular surface health approach - Hanan Awad Alkozi; Saleh Alshammeri (PeerJ)
Background Optimal sleep is essential for maintaining physiological homeostasis, and its disruption is associated with numerous physical and mental health issues. Previous studies have linked poor sleep quality to ocular conditions such as dry eye. However, the relationship between sleep quality and vision-related quality of life remains underexplored. This study aimed to investigate the association between ocular surface health and sleep quality, and how both factors relate to vision-related quality of life. Methods Ethical approval was granted by the Deanship of Graduate Studies and Scientific Research at Qassim University (reference no. 21-20-09), and the study was conducted in accordance with the Declaration of Helsinki. Young adult participants completed three questionnaires: the Pittsburgh Sleep Quality Index, the National Eye Institute Visual Function Questionnaire, and the Ocular Surface Disease Index. Ocular surface assessments were conducted using the Keratograph 5M and the Schirmer test to measure tear production. Results Analysis revealed significant correlations between ocular symptoms and vision-related quality of life (Spearman’s r = 0.47, p < 0.0001, n = 93), sleep efficiency (r = 0.22, p < 0.05, n = 75), and sleep disturbances (r = 0.25, p < 0.05, n = 75). A significant negative correlation was also found between sleep quality and vision-related quality of life (r = −0.31, p < 0.005, n = 75). These findings highlight the impact of sleep quality on ocular health, particularly the ocular surface. Conclusion The results suggest a meaningful link between sleep quality, ocular surface health, and vision-related quality of life. Further research is needed to clarify the causal mechanisms and risk factors contributing to ocular discomfort and its effects on visual well-being.